2021
DOI: 10.1002/ejic.202100047
|View full text |Cite
|
Sign up to set email alerts
|

Mixed‐Metal Monophosphate Tungsten Bronzes Containing Rhodium and Iridium

Abstract: Solution combustion synthesis followed by annealing in air led to the MPTB-related phosphates (Rh 1/6 W 5/6 O 3 ) 8 (PO 2 ) 4 , (Ir 1/6 W 5/ 6 O 3 ) 8 (PO 2 ) 4 (a = 5.258(2) Å, b = 6.538(3) Å, c = 17.322(8) Å), (Rh 1/ 9 W 8/9 O 3 ) 12 (PO 2 ) 4 and (Rh 2/21 W 19/21 O 3 ) 14 (PO 2 ) 4 . Single-crystals of the mixed-metal (Rh,W)-MPTBs at m = 4 and at m = 7 were grown by chemical vapor transport (CVT). Their crystal structures have been refined from X-ray single-crystal data {(Rh,W

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Unsupported ruthenium tungsten phosphates were synthesized by solution combustion synthesis (SCS) and subsequent calcination and are listed in Supporting Information Table S1 (Concept A). An exhaustive structure study of ReO 3 -type tungsten phosphates containing PGMs can be found in ref. Figure a shows the XRD pattern of all (Ru 0.1 W 0.4 P 0.5 )­O 2.5+δ samples calcined at low (450 °C), middle (550–700 °C), and high (900 °C) temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…Unsupported ruthenium tungsten phosphates were synthesized by solution combustion synthesis (SCS) and subsequent calcination and are listed in Supporting Information Table S1 (Concept A). An exhaustive structure study of ReO 3 -type tungsten phosphates containing PGMs can be found in ref. Figure a shows the XRD pattern of all (Ru 0.1 W 0.4 P 0.5 )­O 2.5+δ samples calcined at low (450 °C), middle (550–700 °C), and high (900 °C) temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, they also find applications due to their electrochromic [2,3] and catalytic properties after heterovalent mixed-metal (mm) tandem replacing W V by (M IV 1/2 W VI 1/2 ), (M III 1/3 W VI 2/3 ), or (M II 1/4 W VI 3/4 ). [4,5] The molybdenum bronzes became very popular in the 80's as they provided the first examples of oxide compounds materializing CDW physics. [6] This was subsequently discovered in the tungsten bronzes, which have become outstanding reference materials ever since.…”
Section: Introductionmentioning
confidence: 99%
“…Since this early discovery, they have turned into a compulsory family of related mixed valence tungsten and molybdenum oxides, based on the diversity of structural variants and displaying a number of fundamental properties, which most notably include charge‐density‐wave (CDW) orders assisted by Peierls like transitions, as well as superconductivity and some interesting similarities with the high‐ T c cuprates. In addition, they also find applications due to their electrochromic [2, 3] and catalytic properties after heterovalent mixed‐metal (mm) tandem replacing W V by (M IV 1/2 W VI 1/2 ), (M III 1/3 W VI 2/3 ), or (M II 1/4 W VI 3/4 ) [4, 5] …”
Section: Introductionmentioning
confidence: 99%